Clinical and Biochemical Manifestations of Depression: Relation to the Neurobiology of Stress - Phillip W. Gold; Rodrigo Machado-Vieira; Maria G. Pavlatou (Neural Plasticity)
Major depressive disorder (MDD) is a chronic, recurrent, and severe psychiatric disorder with high mortality and medical comorbidities. Stress-related pathways have been directly involved in the pathophysiology and treatment of MDD. The present paper provides an overview on the stress system as a model to understand key pathophysiological paradigms in MDD. These mechanisms involve behavioral, cognitive, and systemic manifestations and are also associated with the mechanisms of action of effective antidepressants. Aspects such as depression subtypes, inflammation, insulin resistance, oxidative stress, and prothrombotic states in critical brain circuits and periphery are critically appraised. Finally, new strategies for approaching treatment-resistant major depression and potential adverse effects associated with this complex and intricate network are highlighted. The authors used PubMed as the database for this review. Each author extracted relevant data and assessed the methodological quality of each study.